(untitled) (Journal of Foreign Language Studies, 2022)
There are numerous approaches to teaching writing skills with their own advantages and disadvantages. This study aims to explore an appropriate pedagogical approach to a particular writing course and prove the higher effectiveness of combining different approaches compared to adopting a single one. It focuses on analyzing strengths and limitations of approaches to teaching writing as well as the course objectives to identify proper teaching methods. On that basis, this study considers the adoption of mixed approaches and evaluates the students’ progress. Data were collected from class observations, students’ essays and a survey questionnaire. The research results show that different approaches can be flexibly adopted in a course, contributing to reducing the students’ errors and achieving the course objectives.